2010
DOI: 10.1097/ans.0b013e3181eb41cf
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Whiteness in Nursing Education

Abstract: This article describes a project designed to change the climate of whiteness in academic nursing. Using an emancipatory, antiracist perspective from whiteness studies, we describe a project that helped faculty and staff to work together to challenge and begin to change the status quo of unnamed white privilege and racial injustice in nursing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…The evidence could then be used to advocate for structural interventions aimed at altering imbalances of power, such as the provision of micro-financing programs to reduce economic inequality 1 or antiracist education to challenge and change the unmarked white privilege of the US healthcare system. 47 …”
Section: Introductionmentioning
confidence: 99%
“…The evidence could then be used to advocate for structural interventions aimed at altering imbalances of power, such as the provision of micro-financing programs to reduce economic inequality 1 or antiracist education to challenge and change the unmarked white privilege of the US healthcare system. 47 …”
Section: Introductionmentioning
confidence: 99%
“…It is important that nursing students critique the taken-for-granted reference point against which patients are measured and that they be aware of the mechanisms underlying unequal relationships in society and health-care (Boutain, 2005). One way inequalities are created is through the construction of an unquestioned "normality," as opposed to different "others" (Kumashiro, 2000), in the form of white, middle-class, female nursing (Schroeder & DiAngelo, 2010). The three discourses revealed the teachers' unawareness of this antithetical relationship.…”
Section: The Invisible "Normality" Of Nursing Teachersmentioning
confidence: 99%
“…Conceptions of the "normal" are thereby reproduced, and a discursive order of normality continues to guide the education of nursing students. Schroeder and DiAngelo (2010) concluded that an ongoing retreat from the discomfort of authentic racial engagement results in a perpetual cycle that serves to keep racism in place. This can be transferred to the present study: it would be easy to refrain from questioning restricting norms just because doing so is uncomfortable.…”
Section: ) This Critical Consciousness Concerns Structural Oppressmentioning
confidence: 99%
See 2 more Smart Citations